Preparation and application of sodium ferric sulfate pyrophosphate composite polyanion positive electrode new material of sodium ion battery

By introducing the synergistic effect between pyrophosphate and sulfate into the sulfate polyanionic cathode material of sodium ion battery, and using spray-drying in-situ carbon coating technology, the problem of easy decomposition of the material and by-product generation in high temperature environments is solved, and the high thermal stability and electrochemical performance of the material are improved.

CN120149382APending Publication Date: 2025-06-13BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510518125.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Sodium ion battery sulfate polyanionic cathode materials are easily decomposed under high temperature environments, resulting in hindered electron conduction and easily form by-products during sintering, reducing electrochemical performance.

Method used

The synergistic effect between pyrophosphate and sulfate is introduced through spray drying technology, which improves the thermal stability and electrochemical performance of composite materials, and adopts cost-effective spray drying in-situ carbon coating technology to reduce production costs.

Benefits of technology

It significantly improves the thermodynamic stability and electrochemical properties of the material, extends the cycle life of the material, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120149382A_ABST
    Figure CN120149382A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion battery materials, and discloses preparation and application of a sodium-ion battery ferric sodium sulfate pyrophosphate composite polyanion positive electrode new material. The invention aims to solve the preparation problems that the traditional sulfate polyanion material is easy to decompose at high temperature and the in-situ coating of biochar is difficult to realize, and the excellent electrochemical activity of the sulfate polyanion material is verified through experiments. Specifically, the Na2FeP2O7SO4-700 electrode material disclosed by the invention shows the initial discharge capacity of 68.40 mAh / g at the discharge rate of 0.05 C, and shows the potential value of the Na2FeP2O7SO4-700 electrode material in the application of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation and application of a new composite polyanion cathode material of sodium iron pyrophosphate sulfate for sodium-ion batteries, belonging to the technical field of sodium-ion batteries. Background Art

[0002] With the acceleration of the global energy transition and the urgent need for sustainable development, the development of efficient and low-cost energy storage technologies has become the key to solving energy supply fluctuations and environmental problems. As a new energy storage technology, sodium-ion batteries have received extensive attention due to their rich resources, low cost, and similar working principles to existing lithium-ion batteries. Sodium-ion batteries are considered to have broad application prospects in fields such as large-scale energy storage, low-speed electric vehicles, and distributed energy systems. In the field of sodium-ion batteries, polyanion cathode materials have become a research hotspot due to their unique structural characteristics and excellent electrochemical performance. Among them, sulfate-based polyanion materials such as Alluaudite-type Na 2 Fe 2 (SO 4 ) 3 and Eldfellite-type NaFe(SO 4 ) 2 , with their relatively high discharge platforms, excellent cycle performance, and economic advantages, show great potential for development. However, these materials still face multiple technical challenges in the process of industrial application.

[0003] First of all, in the material structure, the FeO 6 octahedrons are connected by insulating SO 4 groups, resulting in blocked electron conduction, so that the capacity retention rate of the material is low and the attenuation is obvious during high-rate charge and discharge. Secondly, sulfate-based materials are prone to sulfate decomposition and release of SO x gas in a high-temperature environment, which restricts the implementation of high-temperature carbon coating modification processes. In addition, by-products such as Fe 3 O 4 or Na 6 Fe(SO 4 ) 4 are easily formed during the sintering process of the material, thereby reducing the electrochemical performance of the material. Although the conductivity can be improved by ultrasonic dispersion of conductive materials with sodium sulfate and ferrous sulfate aqueous solutions followed by low-temperature sintering, due to the hydrophobic characteristics of conductive carbon materials, it is difficult to achieve uniform dispersion solely by ultrasonic treatment, ultimately resulting in uneven distribution of the conductive network of the composite cathode material and affecting the high-rate performance and cycle life of the battery. Summary of the Invention

[0004] The object of the present invention is to provide a preparation and application of a new sodium iron pyrophosphate sulfate composite polyanion cathode material for sodium-ion batteries. Through the spray-drying technology process, the synergistic effect of pyrophosphate (P 2 O 7 ) and sulfate (SO 4 ) is introduced to improve the thermal stability and electrochemical performance of the composite material. The introduction of pyrophosphate not only strengthens the structural stability of the material, but also optimizes the electron transport channels, effectively inhibiting the decomposition of sulfate materials under high-temperature conditions. At the same time, the present invention adopts an economical and efficient spray-drying in-situ carbon coating technology, avoiding the use of high-cost finished carbon materials and further reducing the production cost. By optimizing the spray-drying preparation process, the molecular-level uniform mixing of elements such as Na, Fe, S, P, and O is achieved, effectively avoiding the generation of impurity phases and greatly improving the comprehensive electrochemical performance of the material. The development of this new sodium iron pyrophosphate sulfate composite polyanion cathode material and its preparation method has important scientific significance and application value for improving the overall performance of sodium-ion batteries and promoting their commercialization process.

[0005] The object of the present invention can be achieved by the following technical solutions:

[0006] A sodium-ion battery prepared from a new sodium iron pyrophosphate sulfate composite polyanion cathode material includes the following steps:

[0007] (1) A sodium source, an iron source, a sulfate, a phosphorus source, an antioxidant and / or a carbon source are fully stirred in deionized water to obtain a yellow suspension. The suspension is subjected to spray-drying treatment to obtain a yellow composite precursor powder.

[0008] (2) The composite precursor powder is placed in a crucible, and the crucible is placed in a tube furnace. The tube furnace is heated to 500-700 °C in an inert atmosphere and calcined for 8-12 h. After the calcination is completed, it is cooled to room temperature, and the powder in the crucible is collected to obtain a new sodium iron pyrophosphate sulfate composite cathode material.

[0009] (3) At room temperature, first, a working electrode is prepared. The cathode material, a conductive agent and a binder are mixed into a uniform slurry in NMP at a ratio of 7:2:1; the obtained slurry is evenly coated on an aluminum foil with a scraper and dried in a vacuum oven at 100 °C for 12 h to obtain a working electrode; finally, it is cut into a disc with a diameter of 1.1 cm as the cathode material with a punching machine, a sodium sheet as the anode material, 1M NaClO 4 EC:PC = 1:1 and 5 vol% FEC as the electrolyte, and glass fiber as the separator to prepare a button battery. The electrochemical performance test is completed under the detection of a Neware system. The test voltage range is 1.5-4.5 V, the test temperature is 30 °C, and the current density is 0.05C-0.5C (1C = 105 mA / g).

[0010] Further, in step (1), the sodium source is sodium carbonate, the iron source is ferric nitrate nonahydrate, the sulfate is ammonium sulfate, and the phosphorus source is diammonium hydrogen phosphate.

[0011] Further, in step (1), the molar ratio of sodium carbonate to ammonium sulfate is 1.5 - 2.5:1, the molar ratio of ferric nitrate nonahydrate to ammonium sulfate is 1 - 4:1, and the molar ratio of diammonium hydrogen phosphate to ammonium sulfate is 1 - 3:1. The chemical formula of the prepared cathode material is Na a Fe b (PO 4 ) c SO 4 , where 3 ≤ a ≤ 5, 1 ≤ b ≤ 4, and 1 ≤ c ≤ 3.

[0012] Further, in step (1), the antioxidant can be citric acid or ascorbic acid, and the molar ratio of citric acid to ferric nitrate nonahydrate is 1:10.

[0013] Further, in step (1), the carbon source accounts for 0 - 5% of the mass of sodium iron pyrophosphate sulfate, and the carbon source can be glucose, maltose, or sucrose.

[0014] Further, in step (1), the spray drying temperature is 180 - 200 °C.

[0015] Further, in step (1), the inert atmosphere is Ar or N 2 .

[0016] Further, in step (2), the calcination heating rate is 3 °C / min.

[0017] Beneficial effects

[0018] The present invention discloses a new cathode material for sodium-ion batteries, sodium iron pyrophosphate sulfate (Na 2 Fe 2 P 2 O 7 SO 4 ). In the preparation process of this material, a spray drying combined with calcination process is adopted. By introducing pyrophosphate groups (P 2 O 7 ), a new composite polyanion cathode material of sodium iron pyrophosphate sulfate is successfully designed. This innovative design greatly improves the thermodynamic stability of the material and effectively inhibits the decomposition of sulfate radicals during the high-temperature synthesis process. In addition, the spray drying process can achieve in-situ uniform coating of low-cost biomass carbon under high-temperature conditions, which not only reduces the production cost but also significantly improves the electronic conductivity of the material. Experimental data show that the Na 2 Fe 2 P2 O 7 SO 4 The initial discharge specific capacity of the -700 material can reach 68.40 mAh / g at a discharge rate of 0.05C. The present invention not only overcomes the problem of the high-temperature stability of traditional sulfate cathode materials, but also opens up a new way for improving the performance and reducing the cost of sodium-ion batteries. Description of the Drawings

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments will be briefly introduced below.

[0020] Figure 1 and Figure 2 are SEM images of the Na 2 Fe 2 P 2 O 7 SO 4 -700 material in Example 1.

[0021] Figure 3 are EDS images of the Na 2 Fe 2 P 2 O 7 SO 4 -700 material in Example 1.

[0022] Figure 4 are the rate performance tests of the Na 2 Fe 2 P 2 O 7 SO 4 -700 cathode material in Example 1. Detailed Description of the Embodiments

[0023] The present invention will be further described in detail below in conjunction with specific embodiments.

[0024] Example 1

[0025] Preparation of the Na 2 Fe 2 P 2 O 7 SO 4 -700 material:

[0026] Weigh sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate according to a molar ratio of 1:2:1:2, add them to deionized water, and continuously stir for 2 - 3 h. During this period, add an appropriate amount of citric acid according to a molar ratio of citric acid to iron(III) nitrate nonahydrate of 10:1. Subsequently, a yellow and uniformly dispersed mixed suspension of sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate is obtained. Dry the suspension in a spray dryer at 200 °C to obtain a light yellow solid powder, and then vacuum dry it in a vacuum oven at 100 °C for 12 h to obtain the precursor powder. Sinter the precursor powder in a tubular furnace with an argon atmosphere at 700 °C for 10 h and then cool it to room temperature to obtain Na 2 Fe 2 P 2 O 7 SO 4 -700 composite cathode material.

[0027] Figure 1 and Figure 2 For Example 1, the SEM image of the prepared Na 2 Fe 2 P 2 O 7 SO 4 -700 material shows that the composite material has an irregular spherical morphology.

[0028] Figure 3 For Example 1, the EDS image of the prepared Na 2 Fe 2 P 2 O 7 SO 4 -700 material shows that the distribution of each element in this material is relatively uniform.

[0029] The electrochemical performance of the assembled battery is shown in Table 1. It can be seen from the table that the initial discharge capacity of Example 1 at 0.05C is 68.40 mAh / g.

[0030] Example 2

[0031] Prepare Na 2 Fe 2 P 2 O 7 SO 4 -600 material:

[0032] Weigh sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate according to a molar ratio of 1:2:1:2, add them to deionized water, and continuously stir for 2 - 3 h. During this period, add an appropriate amount of citric acid according to a molar ratio of citric acid to iron(III) nitrate nonahydrate of 10:1. Subsequently, a yellow and uniformly dispersed mixed suspension of sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate is obtained. Dry the suspension in a spray dryer at 200 °C to obtain a light yellow solid powder, and then vacuum dry it in a vacuum oven at 100 °C for 12 h to obtain the precursor powder. Sinter the precursor powder in a tubular furnace with an argon atmosphere at 600 °C for 10 h and then cool it to room temperature to obtain Na 2 Fe 2 P 2 O 7 SO 4 -600 composite cathode material.

[0033] The electrochemical performance of the assembled battery is shown in Table 1. It can be seen from the table that in Example 2, the initial discharge capacity at 0.05C is 33.37 mAh / g.

[0034] Example 3

[0035] Prepare Na 2 Fe 2 P 2 O 7 SO 4 -500 material:

[0036] Weigh sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate according to a molar ratio of 1:2:1:2, add them to deionized water, and continuously stir for 2 - 3 h. During this period, add an appropriate amount of citric acid according to a molar ratio of citric acid to iron(III) nitrate nonahydrate of 10:1. Subsequently, a yellow and uniformly dispersed mixed suspension of sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate is obtained. Dry the suspension in a spray dryer at 200 °C to obtain a light yellow solid powder, and then vacuum dry it in a vacuum oven at 100 °C for 12 h to obtain the precursor powder. Sinter the precursor powder in a tubular furnace with an argon atmosphere at 500 °C for 10 h and then cool it to room temperature to obtain Na 2 Fe 2 P 2 O 7 SO 4 -500 composite cathode material.

[0037] The electrochemical performance of the assembled battery is shown in Table 1. It can be seen from the table that in Example 3, the initial discharge capacity at 0.05C is 33.11 mAh / g.

[0038] Example 4

[0039] Prepare Na 2 Fe 2 P2 O 7 SO 4 / C-700 material:

[0040] Weigh sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate according to a molar ratio of 1:2:1:2, add them to deionized water, and continuously stir for 2 - 3 h. During this period, add an appropriate amount of citric acid and 5 wt% glucose according to a molar ratio of citric acid to iron(III) nitrate nonahydrate of 10:1. Subsequently, a yellow and uniformly dispersed mixed suspension of sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate is obtained. Dry the suspension in a spray dryer at 200 °C to obtain a light yellow solid powder, and then vacuum dry it in a vacuum oven at 100 °C for 12 h to obtain the precursor powder. Sinter the precursor powder in a tubular furnace with an argon atmosphere at 700 °C for 10 h and then cool it to room temperature to obtain Na 2 Fe 2 P 2 O 7 SO 4 / C-700 composite cathode material.

[0041] The electrochemical performance of the assembled battery is shown in Table 1. It can be seen from the table that the initial discharge capacity of Example 4 at 0.05C is 52.36 mAh / g.

[0042] Example 5

[0043] Prepare Na 2 Fe 2 P 2 O 7 SO 4 / C-600 material:

[0044] Weigh sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate according to a molar ratio of 1:2:1:2, add them to deionized water, and continuously stir for 2 - 3 h. During this period, add an appropriate amount of citric acid and 5 wt% glucose according to a molar ratio of citric acid to iron(III) nitrate nonahydrate of 10:1. Subsequently, a yellow and uniformly dispersed mixed suspension of sodium carbonate, iron(III) nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate is obtained. Dry the suspension in a spray dryer at 200 °C to obtain a light yellow solid powder, and then vacuum dry it in a vacuum oven at 100 °C for 12 h to obtain the precursor powder. Sinter the precursor powder in a tubular furnace with an argon atmosphere at 600 °C for 10 h and then cool it to room temperature to obtain Na 2 Fe 2 P 2 O 7 SO 4 / C-600 composite cathode material.

[0045] The electrochemical performance of the assembled battery is shown in Table 1. As can be seen from the table, the first discharge capacity of Example 5 at 0.05C is 63.13 mAh / g.

[0046] Example 6

[0047] Prepare Na 2 Fe 2 P 2 O 7 SO 4 / C-500 material:

[0048] Weigh sodium carbonate, ferric nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate according to a molar ratio of 1:2:1:2 and add them to deionized water. Continuously stir for 2 - 3 h. During this period, add an appropriate amount of citric acid and 5 wt% glucose according to a molar ratio of citric acid to ferric nitrate nonahydrate of 10:1. Subsequently, a yellow and uniformly dispersed mixed suspension of sodium carbonate, ferric nitrate nonahydrate, ammonium sulfate, and diammonium hydrogen phosphate is obtained. Dry the suspension in a spray dryer at 200°C to obtain a light yellow solid powder. Then, vacuum dry it in a vacuum oven at 100°C for 12 h to obtain the precursor powder. Sinter the precursor powder in a tubular furnace with an argon atmosphere at 500°C for 10 h and then cool it to room temperature to obtain Na 2 Fe 2 P 2 O 7 SO 4 / C-500 composite cathode material.

[0049] The electrochemical performance of the assembled battery is shown in Table 1. As can be seen from the table, the first discharge capacity of Example 6 at 0.05C is 34.24 mAh / g.

[0050] Comparative Example 1

[0051] Prepare Na 2+2x Fe 2-x (SO 4 ) 3 -1 material:

[0052] Dissolve sodium sulfate and ferrous sulfate heptahydrate in 25 ml of deionized water according to a molar ratio of 1:1, and stir for 2 - 3 h until completely dissolved. Add an appropriate amount of ascorbic acid and glucose during the stirring process, and continue to stir for 10 min until the solution becomes clear. Subsequently, dropwise add the above mixed solution into 100 ml of ethanol solution to form a grayish-green precipitate. Wash the precipitate with ethanol, filter it, and dry it at 60°C for 12 h to obtain the precursor powder. Finally, place the precursor powder in an argon atmosphere, calcine it at 350°C for 2 h, and then cool it to room temperature to obtain the product Na 2+2x Fe 2-x (SO 4 ) 3-1 material.

[0053] Mix the above-prepared Na 2+2x Fe 2-x (SO 4 ) 3 -1 cathode material, conductive agent and binder in a mass ratio of 7:2:1 to form a uniform black slurry. Use a spatula to evenly coat the slurry on the aluminum foil and dry it in a vacuum oven at 100 °C for 10 h to obtain a working electrode. Cut the dried working electrode into circular positive electrode sheets with a diameter of 1.1 cm. Use sodium sheets as the negative electrode material, 1 M NaClO 4 (EC:PC = 1:1, containing 5% FEC) as the electrolyte, and glass fiber as the separator to assemble a button battery. The electrochemical performance test is carried out under a Neware system. The test voltage range is 2.0 - 4.5 V, the test temperature is 30 °C, and the current density is 0.1 C (1 C = 100 mA / g)

[0054] The electrochemical performance of the battery assembled in Comparative Example 1 has a discharge capacity of 22.5 mAh / g at 0.1 C.

[0055] Comparative Example 2

[0056] Prepare Na 2+2x Fe 2-x (SO 4 ) 3 -2 material:

[0057] Dissolve sodium sulfate and ferrous sulfate heptahydrate in 25 ml of deionized water according to a molar ratio of 1:2 and stir for 2 - 3 h until completely dissolved. Add an appropriate amount of ascorbic acid and glucose during the stirring process and continue stirring for 10 min until the solution is clear. Subsequently, slowly add the above mixed solution dropwise to 100 ml of ethanol solution to form a gray-green precipitate. Wash the precipitate with ethanol, filter it, and dry it at 60 °C for 12 h to obtain a precursor powder. Finally, place the precursor powder in an argon atmosphere, calcine it at 350 °C for 2 h, and then cool it to room temperature to obtain the product Na 2+2x Fe 2-x (SO 4 ) 3 -2 material.

[0058] Mix the above-prepared Na 2+2x Fe 2-x (SO 4 ) 3The positive electrode material, conductive agent, and binder were mixed at a mass ratio of 7:2:1 to form a uniform black slurry. The slurry was evenly coated on aluminum foil using a scraper and dried in a vacuum oven at 100 °C for 10 h to obtain the working electrode. The dried working electrode was cut into circular positive electrode sheets with a diameter of 1.1 cm. Using sodium sheets as the negative electrode material, 1 M NaClO 4 (EC:PC = 1:1, containing 5% FEC) as the electrolyte, and glass fiber as the separator, a button battery was assembled. The electrochemical performance test was carried out under a Neware system. The test voltage range was 2.0 - 4.5 V, the test temperature was 30 °C, and the current density was 0.1 C (1 C = 100 mA / g)

[0059] The electrochemical performance of the battery assembled in Comparative Example 2 had a discharge capacity of 21.0 mAh / g at 0.1 C.

[0060] Table 1 shows the electrochemical performance test results of the sodium-ion battery half-cells in the examples. The results show that the introduction of pyrophosphate can enhance the thermodynamic stability of sulfate, enabling in-situ coating of biochar under high-temperature conditions. The introduction of the composite anion not only increases the transport rate of Na + ions but also brings a higher discharge specific capacity. Compared with Na 2 Fe 2 (SO 4 ) 3 , the Na 2 FeP 2 O 7 SO 4 material exhibits more stable performance, which may be due to its superior crystal structure and Na + diffusion channels.

[0061] Table 1 Electrochemical performance test results of half-cells

[0062] Case Initial discharge capacity at 0.05C Example 1 68.40 mAh / g Example 2 33.37 mAh / g Example 3 33.11 mAh / g Example 4 52.36 mAh / g Example 5 63.13 mAh / g Example 6 34.24 mAh / g

[0063] As can be seen from Table 1, for the sodium-ion battery prepared in Example 1, at a current density of 0.05 C, the first-cycle discharge specific capacity reached 68.40 mAh / g, indicating that the Na 2 FeP 2 O 7 SO 4 -700 composite positive electrode material can achieve efficient reversible deintercalation and intercalation of Na + .

[0064] From Figure 4It can be seen that at low current densities of 0.05C, 0.1C, 0.2C, and 0.5C, the discharge specific capacity of this material performs well. However, at higher current densities (such as 1.0C and 2.0C), the discharge specific capacity decreases significantly. This indicates that the inherent low electronic conductivity of the polyanion-type material limits its capacity performance under high-current conditions.

[0065] Based on the results of Table 1 and Figure 4 it can be inferred that although Na 2 FeP 2 O 7 SO 4 materials exhibit good performance at low rates, their discharge specific capacity at high rates fails to be fully exploited due to the intrinsic low electronic conductivity of the polyanions. Therefore, it is necessary to further explore hierarchical structure design or nanosizing strategies to improve their overall energy storage performance.

[0066] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Those of ordinary skill in the art should understand that the present invention can be appropriately modified and improved without departing from the principles of the present invention.

Claims

1. Preparation and application of a new sodium ion battery sodium iron sulfate pyrophosphate composite polyanion positive electrode material, characterized in that: The sodium ion battery sodium iron sulfate pyrophosphate composite polyanion positive electrode new material is prepared by the following steps: (1) Sodium source, iron source, sulfate, phosphorus source, antioxidant and / or carbon source are fully stirred in deionized water to obtain a yellow suspension, and the suspension is spray-dried to obtain a yellow composite precursor powder. (2) placing the composite precursor powder into a crucible, placing the crucible into a tubular furnace, heating the crucible to 500-700° C. in an inert atmosphere, and calcining the crucible for 8-12 hours. After calcination, cooling the crucible to room temperature is performed, and the powder in the crucible is collected to obtain a Na2FeP2O7SO4 sodium iron sulfate pyrophosphate composite positive electrode material and / or a carbon-coated Na2FeP2O7SO4 / C positive electrode new material.

2. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The sodium ion battery is prepared by the following steps: At room temperature, the working electrode was first prepared by mixing the positive electrode material, conductive agent and binder in NMP in a ratio of 7:2:1 into a uniform slurry; the obtained slurry was evenly coated on the aluminum foil with a scraper and dried in a vacuum oven at 100°C for 12 hours to obtain the working electrode; finally, it was cut into a disc with a diameter of 1.1 cm as the positive electrode, sodium sheet as the negative electrode material, 1M NaClO4 EC:PC=1:1 and 5vol%FEC as the electrolyte, and glass fiber as the diaphragm to prepare a button battery. The electrochemical performance test was completed under the detection of the Xinwei system, with a test voltage range of 1.5-4.5V, a test temperature of 30°C, and a current density of 0.05C~0.5C (1C=105mA / g).

3. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The sodium source is sodium carbonate, the iron source is ferric nitrate nonahydrate, the sulfate is ammonium sulfate, and the phosphorus source is diammonium hydrogen phosphate.

4. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The molar ratio of sodium carbonate to ammonium sulfate is 1.5-2.5:1, the molar ratio of ferric nitrate nonahydrate to ammonium sulfate is 1-4:1, the molar ratio of diammonium hydrogen phosphate to ammonium sulfate is 1-3:1, and the chemical formula of the prepared positive electrode material is Na a Fe b (PO4) c SO4, where 3≤a≤5, 1≤b≤4, 1≤c≤3.

5. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The antioxidant may be citric acid or ascorbic acid, and the molar ratio of citric acid to ferric nitrate nonahydrate is 1:

10.

6. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The carbon source accounts for 0-5% of the mass of the sodium ferric sulfate pyrophosphate, and the carbon source can be glucose, sucrose or maltose.

7. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The spray drying temperature is 180-200°C.

8. The preparation and application of a new sodium ferric sulfate pyrophosphate composite polyanion positive electrode material for sodium ion batteries according to claim 1, characterized in that: The inert atmosphere is Ar or N2.

9. The preparation and application of a new sodium ion battery sodium ferric sulfate pyrophosphate composite polyanion positive electrode material according to claim 1, characterized in that: The calcination heating rate is 3°C / min.